Augmented Categories Of Proceeds Of Crimes In Relation To Money Laundering In Indonesia - Muhammad Al Husaini; Muhammad Anshori Sudirman; Maulana Syekh Yusuf; Muhammad Hutomo (Unram Law Review, 2019)
Money laundering is a serious crime that threatens economic gain and national welfare. This crime is closely related with other crimes, which serve as the providers of illicit funds or illegal wealth. This paper will explore the augmented categories of proceeds of crimes that might lead to money laundering. This paper is a normative descriptive one with statute and conceptual approach. Findings of this paper show that categories of proceeds of crime have been augmented over the years, as mentioned in amendment of the law of money laundering. Including to these augmented categories are “forbidden fruits” generated from common crimes, transnational crimes, white-collar crimes, and other crimes committed in Indonesian territory, as well as outside the territory with the Double Criminality principle.